2013
DOI: 10.4314/agrosh.v13i1.7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Addition of <i>Moringa</i> Leaf By-Product (Leaf-Waste) on Proximate and Sensory Characteristics of Cookies.

Abstract: The effects of incorporation of Moringa leaf fibre (a by-product of leaf processing which contains 24% Crude Fibre by dry weight at 0, 5 and 10 % substitution of wheat flour in cookies was investigated. Three products containing wheat flour: Moringa leaf fibre ratios of 100:0, 95:5, and 90:10 respectively were prepared, and a commercial cookie was used as a standard. Proximate composition of each of the products was determined and sensory evaluation of the cookies was performed on a 7-point hedonic scale (with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
2
0
2
Order By: Relevance
“…This could be due to the fact that people are more familiar with it than chinchin from other composite samples. Otunola et al (2013) similarly reported that control cookies had higher acceptability than Moringa enriched samples, which could be due to the same reason of familiarity with the control. The chinchin produced from composite flour with 12% finger millet flour was rated closely in almost all the quality attributes evaluated.…”
Section: Sensory Evaluation Of Chinchinmentioning
confidence: 84%
“…This could be due to the fact that people are more familiar with it than chinchin from other composite samples. Otunola et al (2013) similarly reported that control cookies had higher acceptability than Moringa enriched samples, which could be due to the same reason of familiarity with the control. The chinchin produced from composite flour with 12% finger millet flour was rated closely in almost all the quality attributes evaluated.…”
Section: Sensory Evaluation Of Chinchinmentioning
confidence: 84%
“…Dengan ditambahkannya bubuk daun kelor pada permen jeli, maka penerimaan produk menjadi menurun. Hal ini sejalan dengan penelitian yang dilakukan oleh Otunola, et al (2013) pada pembuatan cookies dengan moringa leave waste, bahwa dengan ditambahkannya moringa leave waste maka daya terima produk menurun.…”
Section: Hasil Dan Pembahasanunclassified
“…Namun demikian, apabila dibandingkan dengan formula kontrol (F0), permen jeli tanpa penambahan bubuk daun kelor lebih disukai oleh panelis. Hal ini sejalan dengan penelitian yang dilakukan oleh Otunola, et al (2013), di mana cookies tanpa moringa leave waste lebih disukai rasanya dibandingkan dengan cookies yang disubtitusi dengan moringa leave waste.…”
Section: Rasaunclassified
“…After harvesting, fresh MO leaves may be processed into powder by washing, drying in sunlight and pulverizing them into a fine powder. The coarse material left over in the blending (rotary blade chopping) process is usually disposed of, generating significant waste [34]. This study aims to evaluate the effects of three different drying methods on the physical properties, total phenolic contents, total flavonoid contents, and antioxidant activity of extracts from MO leaf waste.…”
Section: Introductionmentioning
confidence: 99%